Electrical properties of yttrium-doped hafnium-zirconium dioxide thin films prepared by solution process for ferroelectric gate insulator TFT application. (5th May 2020) - Mohit,; Haga, Ken-ichi; Tokumitsu, Eisuke
Abstract: Ferroelectric yttrium-doped hafnium-zirconium dioxide (Y-HZO) thin films were fabricated by solution process on Pt/Ti/SiO2 /Si substrates. Both metal–ferroelectric–metal (MFM) structures with Pt top electrode and metal–ferroelectric–semiconductor (MFS) structures with indium tin oxide (ITO) top electrode were fabricated and characterized. Solution-derived Y-HZO films annealed at 600 °C–800 °C showed ferroelectric properties which were confirmed by polarization–voltage loops ( P – V ) and capacitance–voltage ( C – V ) curves. The ferroelectric properties of Y-HZO were superior to those of undoped HZO, Y-doped HfO2 and undoped HfO2 samples. C – V curves showed clear butterfly loops with depletion of top ITO layer in the case of MFS, while no depletion was observed in the case of MFM structures. Large memory window was obtained for MFS structures and ferroelectric properties were observed even after high temperature annealing process during the solution deposition of ITO electrodes. These results suggest that a solution processed Y-HZO is a promising candidate for ferroelectric gate thin film transistor.